3D-Reconstruction and characterization of the pore microstructure within the asphalt FAM using the X-ray micro-computed tomography. (22nd February 2021) - Zhao, Zili; Jiang, Jiwang; Ni, Fujian; Ma, Xiang
Highlights: A mCT Scanning test was employed to achieve accurate air void of FAM specimens. Results of surface-dry method and volumetric method were compared with mCT. Investigate the air void quantity, volume, uniformity and spatial distribution of different FAMs. Analyze the effects of fabrication methods and NMAS of FAMs on pore microstructure. Abstract: Fine aggregate matrix (FAM) is considered as a key component affecting the performance of asphalt mixtures, but there is a lack of systematic research on the sample fabrication methods and the measurement of the air void. This study aims to investigate the internal pore structure of the FAM samples with different nominal maximum aggregate sizes (NMAS) fabricated by three different compaction methods, including Marshall compaction, Superpave gyratory compaction (SGC) and a popular direct compaction method. The three-dimensional microstructures of FAM specimens were reconstructed by the micro-computed tomography (mCT) scanning test. Air void quantity, volume, and spatial distribution of each FAM sample were obtained by analyzing the microstructure. Volumetric method and surface-dry method were also used to measure the air void content. The results show that the surface-dry method shows a better consistence with the mCT method. When comparing the void distribution of FAMs fabricated by different methods, it was found that the specimens prepared by the direct compaction method show different distributions of air voids with that cored from SGC samples, while the Marshall compaction method performed with more instability with respect to the total air voids. Spatial distribution indicated that FAMs fabricated by direct compaction method would have a concentration of void on the top or bottom due to the edge effects of the compacting process. The specimens cored from the SGC samples showed a better uniformity at large particle size. In general, the direct compaction method is recommended in the study of mortar with NMAS no more than 1.18 mm, while, it is better to fabricate FAM specimens cored from SGC samples when the NMAS is larger.